Chronic pretreatment of Kombucha tea attenuates post-ischemic brain edema in a transient model of global cerebral ischemia - Mesgari-Abbasi, Mehran; Eskandari Vaezi, Fatemeh; Hosseinzadeh, Fezzeh (Nutrire : revista de Sociedade Brasileira de Alimentação e Nutrição = journal of the Brazilian Society of Food and Nutrition, 2024)
Purpose Brain ischemia leads to brain edema formation and neurological impairment. Kombucha tea (KT), a fermented beverage, has antioxidant activity and potential health effects. This study investigated the protective impacts of KT pretreatment in transient global brain ischemia. Methods The Wistar male rats were divided into four experimental groups, including sham and ischemic, and two groups treated with KT. The administration of kombucha tea via gavage at doses of 1 and 2 ml/kg per day was conducted for 2 weeks before the induction of transient global cerebral ischemia. The common carotid arteries were occluded for 60 min to induce brain ischemia. Brain edema and infarct volume were assessed after 24 h of reperfusion using the dry–wet method and 2,3,5-triphenyl tetrazolium chloride (TTC) stained, respectively. The enzyme-linked immunosorbent assay (ELISA) method was used to measure malondialdehyde (MDA) levels, total antioxidant capacity (TAC), and antioxidant biomarkers in serum and brain tissue. Neutrophils were counted using a cell counter. Results The study found that KT pretreatment significantly decreased cerebral edema and infarct volume and reduced malondialdehyde (MDA) content in the blood and brain tissue. It also effectively increased TAC and glutathione peroxidase (GPx) levels in both blood and brain tissue. It also improved motor disabilities and decreased neutrophil count in peripheral blood. Conclusions KT pretreatment alleviates brain edema induced by global brain ischemia through decreased lipid peroxidation and increased antioxidant defense capacity. It could be a new approach to prevent stress oxidative damage in brain stroke subjects.